Pemahaman dan Pengalaman Pengguna terhadap Penerapan PACS (Picture Archiving and Communication System) pada Layanan Radiologi - Samsi, Farah Aulia Rahma; Nugroho, Anshor; Mayani, Anita Nur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Picture Archiving and Communication System (PACS) is a computer-based technology designed to manage the acquisition, transmission, storage, distribution, display, and interpretation of medical images across institutions. This system is tightly integrated with imaging processes in the Radiology Department and clinical practices that depend on radiological examinations. At the Radiology Installation of RSUD Panembahan Senopati Bantul, the delivery of radiology results has become more efficient with PACS. For internal hospital patients, results are distributed electronically to radiologists and clinical specialists without printing. However, for referred patients from external hospitals or those being referred out, printed film remains necessary. This study applied a descriptive quantitative design, conducted in the Radiology Installation of RSUD Panembahan Senopati Bantul from May 5th to May 10th, 2025. Respondents consisted of 20 radiographers, and data collection was carried out using a Guttman scale questionnaire. The data were analyzed descriptively, with validity and reliability testing. Findings indicate that most respondents possess a strong understanding and acceptance of PACS, demonstrated by the predominance of “Yes” answers, some reaching 100%. This highlights the system’s optimal utilization and its positive contribution to service speed, patient data security, and workflow efficiency. The majority of respondents confirmed that PACS significantly improves radiology services, though some indicators showed varied responses, suggesting areas for further development.